Response to benralizumab in patients with severe eosinophilic asthma - Velasco-Santos, Jorge Isaac; Nuñez Martinez, Francisco Javier; Martínez-Sánchez, Brian Humberto; Chávez-Lárraga, Alejandro de Jesús (Revista Médica del Instituto Mexicano del Seguro Social, 2026)
Background: Severe asthma represents a significant public health challenge, and monoclonal antibodies such as benralizumab represent an effective therapeutic option for achieving disease control. Objective: To evaluate the effectiveness of benralizumab in patients with severe eosinophilic asthma by assessing changes in fractional exhaled nitric oxide (FeNO), peripheral blood eosinophils, symptom control, forced expiratory volume in 1 second (FEV1), and exacerbation rates six months after treatment initiation. Materials and methods: A prospective observational study was conducted in 11 patients with severe uncontrolled eosinophilic asthma. Clinical outcomes (ACT), quality of life (mini-AQLQ), FEV1, exacerbations, and biomarkers of blood eosinophils and FeNO were assessed at baseline and six months. Results: After six months of benralizumab therapy, > 90% of patients showed significant improvement in quality of life (mini-AQLQ, p < 0.05), and 72.7% achieved better asthma control (ACT, p < 0.05). Exacerbations decreased by 66.9% (p < 0.05). Blood eosinophils decreased by 97.5% (p < 0.05), FeNO by 57% (p < 0.05), and FEV1 increased by 27.7% (p < 0.05). Conclusions: Benralizumab demonstrated significant clinical and inflammatory benefits in this cohort, improving biomarkers, lung function, exacerbation rates, and patient-reported outcomes, supporting its effectiveness in real-world management of severe eosinophilic asthma.